2010
DOI: 10.1109/tmi.2009.2032542
|View full text |Cite
|
Sign up to set email alerts
|

The ${LoG}$ Characteristic Scale: A Consistent Measurement of Lung Nodule Size in CT Imaging

Abstract: Nodule growth as observed in computed tomography (CT) scans acquired at different times is the primary feature to malignancy of indeterminate small lung nodules. In this paper, we propose the estimation of nodule size through a scale-space representation which needs no segmentation and has high intra- and inter-operator reproducibility. Lung nodules usually appear in CT images as blob-like patterns and can be analyzed in the scale-space by Laplacian of Gaussian ( LoG ) kernels. For each nodular pattern the LoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Gaussian fitting has been used to locate and size pulmonary nodules [8], and other studies have shown that the characteristic scale of a Laplacian of Gaussian (LoG) agreed well with radiologists' estimates of nodule size [9], [10]. In this work, we present a fully automated method for estimating the size and location of a nodule using a multiscale LoG filtering approach.…”
Section: Introductionmentioning
confidence: 78%
“…Gaussian fitting has been used to locate and size pulmonary nodules [8], and other studies have shown that the characteristic scale of a Laplacian of Gaussian (LoG) agreed well with radiologists' estimates of nodule size [9], [10]. In this work, we present a fully automated method for estimating the size and location of a nodule using a multiscale LoG filtering approach.…”
Section: Introductionmentioning
confidence: 78%
“…For example, in [21] Gaussian has been used for locate pulmonary nodules, and other studies have shown that the characteristic scale of a Laplacian of Gaussian (LoG) agreed well with radiologistsąŕ estimates of nodule size [22,23]. Kong et al [24] propose a generalized Laplacian of Gaussian (LoG) (gLoG) filter for detecting general elliptical blob structures in images,Miao et al [25] used rank order LoG filter for interest point detection, and Shi et al [2] proposed a dot enhancement filter by combining Hessian matrix and LoG filter.…”
Section: Related Workmentioning
confidence: 99%
“…Technical approaches previously reported for volumetric lung nodule segmentation can be roughly classified into the following eleven categories: 1) thresholding [167,168,[183][184][185][186][187], 2) mathematical morphology [95,98,[188][189][190][191], 3) region growing [174,189,190,[192][193][194], 4) deformable model [195][196][197][198][199][200][201], 5) dynamic programming [202][203][204], 6) spherical/ellipsoidal model fitting [205][206][207][208][209] [220,221], and 11) watersheds [222]. Next, an overview of the technical approaches for lung nodule segmentation is given.…”
Section: Ct Nodules Segmentation Techniquesmentioning
confidence: 99%
“…Then the most stable scale that minimizes Jensen-Shannon divergence [230] computed over the varying scales determines the final outcome. In Diciotti et al [209], the nodule size was estimated by using the multi-scale Laplacian of Gaussian (LoG) fil-tering [231]. The characteristic scale defined over the LoG scale-space was adopted as the lesion's size estimate and as an initialization of their RG-based segmentation method [193].…”
Section: Deformable Model (Dm) Represents a Class Of Segmentation mentioning
confidence: 99%
See 1 more Smart Citation